Protective role of caffeic acid phenethyl ester against tetramethrine-induced toxicity in mice - Gokhan Nur; Haci Ahmet Deveci; Yusuf Ersan; Oguz Merhan; Mumtaz Nazli; Ozlem Nur (Medicine Science, 2016)
The purpose of this study was to determine the biochemical, histopathological and genotoxic effects of tetramethrine, which is widely used in domestic and agricultural activities as well as identify the protective effect of caffeic acid phenethyl ester (CAPE). 30 Swiss albino laboratory mice (Mus musculus) were used in the study. 10 μM/kg tetramethrine, dissolving in 10 mM DMSO (Dimethyl sulfoxide), was intraperitoneally injected to the Tetramethrine group (n = 10). To the CAPE-Tetramethrine group, 10 µM / kg-1 CAPE, dissolving in 1% ethanol, was applied in three days before the experiment and then, CAPE and 10 μM / kg tetramethrine, dissolving in 10 mM DMSO, was intraperitoneally injected. No injection was made to the control group. At the end of the experiment, the rats anaesthetized with diethyl ether were killed by cervical dislocation and their livers and femur were removed for analysis. In the Tetramethrine group; there was no statistical difference between three groups in terms of mitotic index (MI) and micronucleus frequency (P > 0.05). Chromosomal aberration frequency showed an increase in the other two groups compared to the control group (P < 0.05). Although severe degeneration and necrosis areas were identified in the liver, CAPE decreased the severity of degeneration in the Tetramethrine group. While Tetramethrine increased the malondialdehyde (MDA) level in the liver, CAPE decreased MDA and increased the GSH level. We think that CAPE may be used for therapeutic purposes in order to provide a limited protection against the tetramethrine-related detrimental effects in humans and other living organisms. [Med-Science 2016; 5(4.000): 972-8]